Looking at genetic structure and selection signatures of the Mexican chicken population using single nucleotide polymorphism markers. (20th December 2017) - Strillacci, M G; Vega-Murillo, V E; Román-Ponce, S I; López, F J Ruiz; Cozzi, M C; Gorla, E; Cerolini, S; Bertolini, F; Fontanesi, L; Bagnato, A
Abstract: Genetic variation enables both adaptive evolutionary changes and artificial selection. Genetic makeup of populations is the result of a long-term process of selection and adaptation to specific environments and ecosystems. The aim of this study was to characterize the genetic variability of México's chicken population to reveal any underlying population structure. A total of 213 chickens were sampled in different rural production units located in 25 states of México. Genotypes were obtained using the Affymetrix Axiom ® 600 K Chicken Genotyping Array. The Identity by Descent (IBD) and the principal components analysis (PCA) were performed by SVS software on pruned single nucleotide polymorphisms (SNPs). ADMIXTURE analyses identified 3 ancestors and the proportion of the genetic contribution of each of them has been determined in each individual. The results of the Neighbor-Joining (NJ) analysis resulted consistent with those obtained by the PCA. All methods utilized in this study did not allow a classification of Mexican chicken in distinct clusters or groups. A total of 3, 059 run of homozygosity (ROH) were identified and, being mainly short in length (<4 Mb), these regions are indicative of a low inbreeding level in the population. Finally, findings from the ROH analysis indicated the presence of natural selective pressure in the population of Mexican chicken. The study indicates that the Mexican chicken clearly appear to be a unique creole chicken population that was not subjected to a specific artificial selection. Results provide a genetic knowledge that can be used as a basis for the genetic management of a unique and very large creole population, especially in the view of using it in production of hybrids to increase the productivity and economic revenue of family farming agriculture, which is widely present in México.